A Cross-Sectional Study on the Relationship Between Age, Surgery Duration, and Post-Anesthesia Hypothermia Incidenc: English - Narendra, Gangsar Haryo; Sukmaningtyas, Wilis; Burhan, Asmat (LPPM Universitas Harapan Bangsa, 2023)
Background: Hypothermia is a post-anesthesia complication commonly found in the recovery room after general and regional anesthesia. Patients undergoing surgery are at risk of hypothermia. Hypothermia can be defined as a body temperature of less than 36oC. Objective: to identify the relationship between age and length of surgery with the incidence of post-anesthesia hypothermia at Hospital dr.R.Goeteng Taroenadibrata Methods: This research method uses a quantitative approach with a cross-sectional approach. A sample of 86 post-anesthesia respondents with a purposive sampling technique and chi-square test to analyze the data. Results: This study shows a relationship between age and the incidence of hypothermia with a chi-square value with a probability value of 0.001 <0.05. This study also shows a connection between the length of surgery and the incidence of hypothermia at 69% with an X2 value with a probability value of p = 0.001. Conclusion: We confirmed that age and duration of surgery significantly affect patients' thermoregulation after general anaesthesia and regional anaesthesia, resulting in various signs and symptoms.